2010
DOI: 10.1177/1354068809345856
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensional nature of party competition

Abstract: Left-right is a convenient tool for summarizing the complexities of voter-party linkages in a manner that is comparable across contexts and that avoids the pathologies of preference aggregation in higher dimensions. Yet several reasons exist to believe that left-right is increasingly incapable of summarizing political behavior: the inability of left-right to capture policy concerns beyond economics and religion; the accumulation of new issue concerns over time; pressures for policy convergence stemming from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 36 publications
0
47
0
5
Order By: Relevance
“…However, the mobilization and repositioning of parties along the authoritarianlibertarian dimension does not mean that the more traditional economic left-right dimension has disappeared. Rather, new issue areas such as environment, European integration, multiculturalism and immigration as well as libertarian values have led to a change in ideological competition between the parties (Albright 2010;GreenPedersen and Mortensen 2010). Political challenges and issues related to globalization, environmental problems and migration have created other social divisions and stressed complementary ideological dimensions in most European countries -most notably the sociocultural and authoritarian-libertarian dimensions -regarding issues of tolerance and hierarchical social relations (Flanagan and Lee 2003;Kitschelt 1994;Kriesi 2010;Kriesi et al 2006;Stubager 2008).…”
mentioning
confidence: 99%
“…However, the mobilization and repositioning of parties along the authoritarianlibertarian dimension does not mean that the more traditional economic left-right dimension has disappeared. Rather, new issue areas such as environment, European integration, multiculturalism and immigration as well as libertarian values have led to a change in ideological competition between the parties (Albright 2010;GreenPedersen and Mortensen 2010). Political challenges and issues related to globalization, environmental problems and migration have created other social divisions and stressed complementary ideological dimensions in most European countries -most notably the sociocultural and authoritarian-libertarian dimensions -regarding issues of tolerance and hierarchical social relations (Flanagan and Lee 2003;Kitschelt 1994;Kriesi 2010;Kriesi et al 2006;Stubager 2008).…”
mentioning
confidence: 99%
“…Yet, the utility of a single ideological dimension has long been called into question (Stokes, 1963). In fact, several scholars have echoed the idea that a one-dimensional ideological axis simply cannot account for important political cleavages in societies, thereby leading to a significant loss of political information (Albright, 2010;Castles and Mair, 1984;Stokes, 1963). As a result, researchers have pushed forward and analysed politics through two ideological dimensions (see, for example, Inglehart, 1990).…”
Section: Ideologies and Vote Choicementioning
confidence: 96%
“…As Albright (2010) explains, this is done in order to simplify the complexities of politics and to allow for comparisons. Yet, the utility of a single ideological dimension has long been called into question (Stokes, 1963).…”
Section: Ideologies and Vote Choicementioning
confidence: 99%
“…All of this is evidence against an invariant conceptualization of the left-right dimension, which is at the centre of the RILE index. Furthermore, inductive analyses of the manifesto data have shown that policy spaces as captured by these data are highly multidimensional (Albright, 2010). Albright notes that there is no evidence that a single policy dimension exists which can adequately describe the variation between parties.…”
Section: The Nature Of the Left-right Dimensionmentioning
confidence: 99%